Foreign Investors' Rights and Obligations Under the Protection of Investment Act 22 of 2015 - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--Univesrity of Pretoria, 2021.